Modeling of structure and interface controlled strength of laminated metal/graphene composites. (July 2021) - Sheinerman, A.G.
Abstract: A model is suggested that describes the observed dependences of the strength of laminated metal/graphene composites on the lateral size of graphene platelets. Within the model, these dependences are associated with the accumulation of dislocations at metal/graphene interfaces and dislocation pinning by the edges of graphene platelets. It is shown that the strength of laminated metal/graphene composites depends not only on graphene platelet dimensions and the orientation of the applied load but also on the specific energies of metal/graphene interfaces and lamella boundaries. This can enable one to control the strength of laminated metal/graphene composites by tuning their interface properties. Highlights: We model the plastic deformation of laminated metal/graphene composites. The model considers dislocation accumulation and dynamic recovery at lamella boundaries and metal/graphene interfaces. The observed dependences of the flow stress on the platelet length and loading direction are explained. It is shown that the strength of the composites can be controlled by their interface energies.